The Fountainpen and the Metronome: Bloomsbury Dancing, or not - Caroline Marie (Cahiers Victoriens et Edouardiens)
When Lydia Lopokova, the Russian ballerina, married John Maynard Keynes, the world-famous economist, the match met with fierce disapproval on the part of his Bloomsbury friends. It may be argued that the fact that the Bloomsbury set overlooked Lydia Lopokova’s love for words and poetical frame of mind so as to assign the silent part of the muse to her epitomizes the way they failed to fully acknowledge how the grammar of dance might have enriched the more canonical art forms they were familiar with.